THE EFFECT OF BOOKLET – ASSISTED CTL MODEL ON THE STUDENTS’ CREATIVE THINKING ABILITY AT GRADE IV ELEMENTARY SCHOOL - Shinta Dewi; Murtono; Ratri Rahayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the effect of the Contextual Teaching and Learning (CTL) model assisted by booklets on the creative thinking ability of fourth-grade elementary school students. The use of booklet media in the CTL model was considered appropriate for Natural Science and poetry materials in the theme Cita-Citaku. Through the CTL model and booklet media, students could relate the learning materials to their life environment, both in groups and individually. This study employed quantitative experimental research with a nonequivalent posttest-only control group design. The samples in this study were fourth-grade students of SDN 1 Bulungcangkring as the experimental class and fourth-grade students of SDN 3 Bulungcangkring as the control class. The results revealed that (1) the creative thinking ability of students taught with the CTL model assisted by booklets was better than that of students taught with the lecture model; and (2) the average creative thinking ability of students taught with the CTL learning model exceeded the minimum completeness criteria (KKM) of 70. It could be concluded that the Contextual Teaching and Learning model assisted by booklets had a significant effect on improving the creative thinking abilities of fourth-grade elementary school students.